Admission Rate of Patients Visiting Emergency Department in a Tertiary Care Center in Kathmandu - Sanjeeb Tiwari; Jyotshna Sharma Tiwari; Jay Bhushan Jha; Sushant Regmi; Dhirendra Yadav; Ravi Kafle; Inesh Khanal; Aakripa Rani Shrestha; Shubham Shrestha; Yagya Laxmi Shakya; Ramesh Kumar Maharjan; Sanjaya Kumar Gupta (Journal of Nepal Medical Association, 2024)
Introduction: Emergency departments serve as the initial point of contact for patients with a wide range of conditions. Not all patients visiting get admitted to the hospital. The admission rate varies from 20% in the United States to 40.83% in Nepal. Given the variability in these results across different regions, there is a need to better understand the admission rates from the Emergency Department. Methods: A descriptive cross-sectional study was conducted after obtaining ethical approval( Reference Number: 58 (6-11)E2 081/082) in the Emergency Department of a tertiary health care center. Retrospective data was collected from the data register. The data from April 2023 to April 2024 was collected. A sample size of 222 was calculated and convenience sampling was done. Demographic details like age, sex, and data regarding admission status were collected. Data was collected in MS Excel and was analyzed using JASP software. Results: Out of 222 patients that presented to the emergency department, 53 (23.87%)(18.26-29.47,95 % Confidence Interval) were admitted to the ward or intensive care unit of the hospital, whereas 167 (75.23) got discharged, 1 (0.45%) was brought dead and 1 (0.45%) expired. The median age of patients was 43 (IQR: 26-62). The admission rate of females was 20 (17.24%), whereas for males it was 33 (31.13%). Conclusions: The prevalence of admission of patients visiting the emergency department was higher than similar US based studies. There was a higher percentage of female patients presenting to theemergency department, while those being admitted were mostly males.